Lithium negative electrode with multi-layer composite artificial SEI (solid electrolyte interface) film as well as preparation method and application of lithium negative electrode

By using a lithium negative electrode with a multi-layer composite artificial SEI film in the lithium battery, the problems of lithium dendrites growth, low ion conductivity and poor stability are solved, and the high cycle performance, safety and efficiency of the lithium battery are achieved.

CN119673947AActive Publication Date: 2025-03-21TIANFU JIANGXI LAB

Patent Information

Application Number
CN202411818728.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-21
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

During the charging and discharging process, lithium metal negative electrodes have problems such as lithium dendrites growth, low ion conductivity, poor stability and mechanical properties, resulting in limited battery cycle life, safety and energy density.

Method used

The lithium negative electrode with a multi-layer composite artificial SEI film is used to build a lithium-friendly sponge-type porous structure, which increases the lithium deposition space, inhibits the growth of lithium dendrites, and builds a high-stability, excellent ionic conductivity and mechanical strength artificial SEI layer through multifunctional inorganic composite materials.

Benefits of technology

It significantly improves the circulation performance, safety and overall efficiency of lithium batteries, extends the cycle life of the battery, improves the conductivity and mechanical strength of lithium ions, and reduces the irreversible loss of lithium metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673947A_ABST
    Figure CN119673947A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium negative electrode with a multi-layer composite artificial SEI film and a preparation method and application of the lithium negative electrode, and relates to the technical field of lithium batteries. Comprising a porous material, a lithium-loving layer, lithium metal and an inorganic composite material, a lithium-loving layer and lithium metal are sequentially deposited on one side of the porous material, and an inorganic composite material is deposited on the other side of the porous material; the porous material is at least one of a porous carbon material and a porous silicon material; the inorganic composite material is at least five of LiF, Li2O, Li3N, Li2CO3, Li2S, Li10GeP2S12 and Li3PO4, and the inorganic composite material is at least five of Li2CO3, Li2S, Li10GeP2S12 and Li3PO4. According to the invention, the lithium-loving sponge-like porous structure is constructed, the lithium deposition space is increased, the growth of lithium dendrites is effectively inhibited, the SEI layer is prevented from being punctured, and meanwhile, the artificial SEI layer with high stability, excellent ionic conductivity and mechanical strength is constructed by adopting the multifunctional inorganic composite material, so that the cycle performance, the safety and the overall efficiency of the lithium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium negative electrode with a multi-layer composite artificial SEI film, and a preparation method and application thereof. Background Art

[0002] Currently, lithium metal anodes have the following problems during the charge and discharge cycle, which limits the cycle life, safety and energy density of the battery.

[0003] 1. During the charging and discharging process of lithium metal negative electrodes, non-uniform lithium deposition often occurs, leading to the growth of lithium dendrites. These dendrites will not only pierce the solid electrolyte (SEI) layer, but may also penetrate the battery separator, causing internal short circuits. The growth of lithium dendrites is one of the main causes of battery thermal runaway, and even fires and explosions, and other safety accidents, seriously affecting the safety and cycle performance of the battery.

[0004] 2. An unstable SEI layer is often formed on the negative electrode surface. This SEI layer is constantly broken and rebuilt during the battery charging and discharging process, resulting in reduced ion conductivity. The naturally generated SEI layer is usually uneven in thickness and has low ion conductivity. It cannot effectively support efficient ion migration, resulting in increased performance degradation of the battery under high-rate charging and discharging.

[0005] 3. The current SEI layer is generally fragile and fragile, and cannot remain stable during long-term charge and discharge cycles. As the battery cycles, the SEI layer will gradually break and rebuild, which not only increases the internal resistance of the battery, but also leads to direct contact between the negative electrode and the electrolyte, which in turn triggers side reactions and accelerates the irreversible loss of lithium. Therefore, the structural stability of the SEI layer directly affects the cycle life and efficiency of the battery.

[0006] 4. The SEI layer in the prior art often cannot provide sufficient mechanical strength to maintain structural integrity when facing the expansion and contraction of the negative electrode. During the battery charging and discharging process, the lithium metal negative electrode will undergo volume changes, which will cause cracks and peeling in the SEI layer, further exacerbating the battery performance degradation. Due to the poor mechanical properties of the existing SEI layer, it cannot effectively adapt to the volume changes of the lithium metal negative electrode, causing the battery to fail after multiple cycles.

[0007] Due to the existence of the above technical defects, the practical application of lithium metal anode is greatly limited. Based on this, a lithium anode with a multi-layer composite artificial SEI film is proposed to solve the above problems. Summary of the invention

[0008] The present invention aims to solve the technical problems in the prior art that lithium metal negative electrodes have lithium dendrite growth, low ion conductivity, poor stability and mechanical properties. The present invention aims to provide a lithium negative electrode with a multilayer composite artificial SEI film and a preparation method and application thereof. By constructing a lithium-philic sponge-like porous structure, the lithium deposition space is increased, the growth of lithium dendrites is effectively inhibited, and it is prevented from piercing the SEI layer. At the same time, a multifunctional inorganic composite material is used to construct an artificial SEI layer with high stability, excellent ionic conductivity and mechanical strength, thereby improving the cycle performance, safety and overall efficiency of the lithium battery.

[0009] The present invention is achieved through the following technical solutions:

[0010] The first object of the present invention is to provide a lithium negative electrode having a multi-layer composite artificial SEI film, comprising a porous material, a lithium-philic layer, lithium metal and an inorganic composite material;

[0011] A lithium-philic layer and lithium metal are sequentially deposited on one side of the porous material, and an inorganic composite material is deposited on the other side of the porous material;

[0012] The porous material is at least one of a porous carbon material and a porous silicon material;

[0013] The inorganic composite material is LiF, Li2O, Li3N, Li2CO3, Li2S, Li 10 GeP2S 12 , Li3PO4, or at least five of the following.

[0014] Furthermore, the pore size of the porous material ranges from 50nm to 100nm.

[0015] Furthermore, the lithium-philic layer material is Ag.

[0016] Furthermore, the inorganic composite material is LiF, Li2O, Li3N, Li2CO3 and Li2S, Li 10 GeP2S 12 A mixture consisting of any one of Li3PO4.

[0017] Furthermore, the mass ratio of each component in the inorganic composite material is LiF:Li2O:Li3N:Li2CO3:(Li2S or Li 10 GeP2S 12 or Li3PO4)=(0.5-2):1:1:1:1.

[0018] The second object of the present invention is to provide a method for preparing a lithium negative electrode having a multi-layer composite artificial SEI film, comprising the following preparation steps:

[0019] Cleaning the porous material to remove organic contaminants followed by nitriding;

[0020] Depositing a lithium-philic material on one side of the porous material to form a lithium-philic layer film;

[0021] depositing lithium metal on the lithiophilic layer;

[0022] An inorganic composite material is deposited on the other side of the porous material, and the material is cooled and solidified to obtain a lithium negative electrode having a multi-layer composite artificial SEI film.

[0023] Furthermore, the cleaning of the porous material comprises the following steps:

[0024] The porous material is cleaned with nitric acid or a mixed acid solution of nitric acid and sulfuric acid, cleaned with deionized water, dried, and finally heated to 400-800° C. in an inert atmosphere to remove organic pollutants on the surface.

[0025] Furthermore, the nitriding treatment comprises the following steps:

[0026] The porous material is immersed in a urea or melamine solution, stirred and dried at 60-80°C, and then heat treated at 600-800°C in a nitrogen or ammonia atmosphere to introduce active nitrogen sites.

[0027] Furthermore, the deposition adopts vacuum evaporation coating technology.

[0028] The third object of the present invention is to provide a lithium negative electrode having a multi-layer composite artificial SEI film for use in a lithium battery.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] 1. The present invention arranges a porous material so that lithium metal can be uniformly deposited in the porous structure and provides space for the growth of lithium dendrites, which can effectively prevent lithium dendrites from piercing the SEI layer; by arranging a lithium-philic layer, a highly active lithium-philic interface is introduced to the surface of the porous material, which significantly reduces the energy barrier for lithium ion migration and improves the ionic conductivity of the interface; a strong artificial SEI layer is formed by introducing an inorganic composite material layer, which not only has excellent chemical stability, but also can significantly improve the mechanical strength of the interface and lithium ion conductivity. Therefore, through the synergistic effect of these structures, the cycle performance, safety and overall efficiency of the lithium battery are effectively improved.

[0031] 2. In the process of preparing the lithium negative electrode, the present invention can enhance the surface activity by removing the organic pollutants on the surface of the porous material, ensure that the subsequent lithium metal can be uniformly deposited in the porous structure, and provide space for the growth of Li dendrites.

[0032] 3. In the process of preparing the lithium negative electrode, the present invention can improve the chemical activity of the porous material and enhance the binding force with subsequent materials by functionalizing the porous material, so that the overall structure can better adapt to volume changes during the battery cycle and reduce interlayer shedding. At the same time, the distribution of surface active sites is optimized, which helps to improve the conduction efficiency of lithium ions in the porous material. After high-temperature treatment, the porous material has excellent mechanical strength and durability.

[0033] 4. In the process of preparing the lithium negative electrode, the present invention introduces a highly active lithium-philic interface by evaporating the lithium-philic layer, which can significantly reduce the energy barrier of lithium ion migration and improve the ionic conductivity of the interface.

[0034] 5. In the process of preparing the lithium negative electrode, the present invention forms a solid artificial SEI layer by introducing an inorganic composite material layer, which not only has excellent chemical stability, but also can significantly improve the mechanical strength and Li ion conductivity of the interface. The inorganic composite material layer prepared by co-evaporation technology has high density and high uniformity, which can effectively isolate the direct contact between the lithium negative electrode and the electrolyte, reduce interfacial side reactions, and extend the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0036] Figure 1 This is a schematic diagram of the structure of a sponge-like multi-layer composite artificial SEI film of the present invention;

[0037] Marks and corresponding parts names in the attached drawings:

[0038] 1-porous materials, 2-lithiophilic layers, 3-lithium metals, 4-inorganic composite materials. DETAILED DESCRIPTION

[0039] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the technical solutions in the embodiments of the present invention are clearly and completely described below in combination with the embodiments and drawings. Obviously, the schematic implementation modes of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0040] The following is a detailed description of the lithium negative electrode with a multi-layer composite artificial SEI film, a preparation method thereof, and an embodiment of the application of the present invention with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions and repeated descriptions of well-known matters are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art.

[0041] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0042] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0043] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0044] Unless otherwise specified, the terms "include" and "comprising" mentioned in this application may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other substances not listed may also be included or only the listed substances may be included.

[0045] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0046] like Figure 1 As shown, the present invention provides a lithium negative electrode with a multi-layer composite artificial SEI film, including a porous material 1, a lithium-philic layer 2, a lithium metal 3 and an inorganic composite material 4;

[0047] A lithium-philic layer 2 and a lithium metal 3 are sequentially deposited on one side of the porous material 1, and an inorganic composite material 4 is deposited on the other side of the porous material 1;

[0048] The porous material 1 is at least one of a porous carbon material and a porous silicon material;

[0049] The inorganic composite material 4 is LiF, Li2O, Li3N, Li2CO3, Li2S, Li 10 GeP2S 12 , Li3PO4, or at least five of the following.

[0050] The present invention arranges a porous material so that lithium metal can be uniformly deposited in the porous structure and provides space for the growth of lithium dendrites, which can effectively prevent lithium dendrites from piercing the SEI layer; by arranging a lithium-philic layer, a highly active lithium-philic interface is introduced to the surface of the porous material, which significantly reduces the energy barrier for lithium ion migration and improves the ionic conductivity of the interface; a strong artificial SEI layer is formed by introducing an inorganic composite material layer, which not only has excellent chemical stability, but also can significantly improve the mechanical strength of the interface and lithium ion conductivity. Therefore, through the synergistic effect of these structures, the cycle performance, safety and overall efficiency of the lithium battery are effectively improved.

[0051] Preferably, the pore size of the porous material 1 is in the range of 50 nm to 100 nm.

[0052] Preferably, the material of the lithium-philic layer 2 is Ag.

[0053] Preferably, the inorganic composite material 4 is LiF, Li2O, Li3N, Li2CO3 and Li2S, Li 10 GeP2S 12 , Li3PO4. Further preferably, the mass ratio of the components in the inorganic composite material 4 is LiF:Li2O:Li3N:Li2CO3:(Li2S or Li 10 GeP2S 12 or Li3PO4)=(0.5-2):1:1:1:1.

[0054] The method for preparing the lithium negative electrode having a multi-layer composite artificial SEI film comprises the following preparation steps:

[0055] S1. Cleaning the porous material to remove organic pollutants: The porous material is cleaned with nitric acid or a mixed acid solution of nitric acid and sulfuric acid, cleaned with deionized water, dried, and finally heated to 400-800° C. in an inert atmosphere to remove surface organic pollutants.

[0056] This step can enhance the surface activity by removing organic pollutants on the surface of the porous material, ensuring that the subsequent lithium metal can be uniformly deposited in the porous structure, providing space for the growth of Li dendrites.

[0057] S2. Functionalization treatment: soak the porous material in urea or melamine solution, stir and dry at 60-80°C, and then heat treat it at 600-800°C in a nitrogen or ammonia atmosphere to introduce active sites such as pyridinic nitrogen and pyrrolic nitrogen to achieve nitridation treatment.

[0058] Optionally, the functionalization treatment can also be oxidized: the porous carbon is immersed in a hydrogen peroxide solution and stirred at 70°C for 2 hours to increase the number of oxygen-containing functional groups on the surface and enhance the hydrophilicity and affinity with other materials.

[0059] The nitriding treatment involves immersing the porous material in a urea or melamine solution while heating and stirring to promote the evaporation of water in the solution, thereby drying the surface of the porous material and fixing the urea or melamine. This method helps to evenly coat the material and avoid uneven deposition.

[0060] Through functional treatment, this step can improve the chemical activity of the porous material, enhance the bonding strength with subsequent materials, make the overall structure more adaptable to volume changes during battery cycling, reduce interlayer shedding, and at the same time, optimize the distribution of surface active sites, which helps to improve the conduction efficiency of lithium ions in the porous material. After high-temperature treatment, the porous material has excellent mechanical strength and durability.

[0061] S3. Lithium-philic layer evaporation coating: Using vacuum evaporation coating technology, lithium-philic material is deposited on one side of the porous material to form a lithium-philic layer film.

[0062] This step introduces a highly active lithium-philic interface through the evaporation coating of the lithium-philic layer, which can significantly reduce the energy barrier of lithium ion migration and improve the ionic conductivity of the interface.

[0063] S4, Li metal evaporation coating: vacuum evaporation coating technology is used to deposit lithium metal on the lithium-philic layer to form a stable lithium negative electrode.

[0064] S5. Co-evaporation of inorganic composite materials: The components of the inorganic composite materials are fully mixed in proportion to form an inorganic composite material. The inorganic composite material is deposited on the other side of the porous material using vacuum evaporation coating technology to form a solid SEI layer. The inorganic composite material is cooled and solidified to obtain a lithium negative electrode with a multi-layer composite artificial SEI film.

[0065] In this step, a solid artificial SEI layer is formed by the introduction of an inorganic composite material layer, which not only has excellent chemical stability, but also can significantly improve the mechanical strength and Li ion conductivity of the interface. The inorganic composite material layer prepared by co-evaporation technology has high density and high uniformity, which can effectively isolate the direct contact between the lithium negative electrode and the electrolyte, reduce interfacial side reactions, and extend the cycle life of the battery.

[0066] In summary, the present invention constructs a lithium-philic sponge-like porous material layer to increase the lithium deposition space, effectively inhibits the growth of lithium dendrites and prevents them from piercing the SEI layer. Through the introduction of inorganic composite materials, an artificial SEI layer with high stability, excellent ionic conductivity and mechanical strength is constructed, which significantly reduces the frequency of repeated formation and rupture of the SEI layer, reduces the irreversible loss of lithium metal, improves the coulombic efficiency and capacity retention rate of the battery, and at the same time, effectively blocks the growth path of lithium dendrites, enhances the overall safety of the battery, and is particularly suitable for high energy density application scenarios.

[0067] The technical solution of the present invention is further described in detail below in conjunction with embodiments.

[0068] It should be noted that the experimental methods used in the examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained by those skilled in the art through commercial channels.

[0069] Example 1

[0070] A method for preparing a lithium negative electrode having a multi-layer composite artificial SEI film comprises the following preparation steps:

[0071] S1: Pretreatment of porous carbon materials

[0072] The porous carbon material (pore size of about 70nm) was placed in a 20% mixed acid (a 1:1 mixture of nitric acid and sulfuric acid), stirred and refluxed for 2-4 hours to ensure that the surface of the material was clean, then washed with deionized water several times until it was neutral and dried; finally, the porous carbon was heated to 600°C in an inert atmosphere (nitrogen) and kept warm for 2 hours to remove organic pollutants on the surface.

[0073] S2: Functionalization

[0074] Prepare a urea solution and soak the porous carbon material in the solution, stir and dry at 60-80°C, then heat treat the soaked porous carbon material in a nitrogen atmosphere at 700°C for 2 hours to introduce active nitrogen sites.

[0075] S3: Lithophilic layer evaporation coating

[0076] The treated porous carbon was fixed at a position 25 cm above the crucible, and the lithium-philic material (Ag) was placed in the crucible. The vacuum environment was controlled to be 10 -5 Pa, crucible heating power is 200W, evaporation rate is Ag is deposited on the surface and in the pores of the porous carbon to form a lithium-philic layer film.

[0077] S4: Li metal evaporation coating

[0078] The porous carbon material with the lithium-philic layer deposited was placed 25 cm above the crucible, and the Li foil was placed in the crucible. The temperature and evaporation rate of the heating source were controlled to make the Li foil evaporate under vacuum (10 -5 Pa) is deposited on the surface of the lithium-philic layer, the crucible heating power is 300 W, and the evaporation rate is

[0079] S5: Preparation of Inorganic Composite Materials

[0080] A composite material of LiF, Li2O, Li3N, Li2CO3, and Li2S was prepared by mixing the materials in a mass ratio of 1:1:1:1:1, and then adding the inorganic composite material into a crucible in a vacuum chamber.

[0081] S6: Co-evaporation deposition of inorganic composite materials

[0082] The other side of the porous material was fixed 25 cm above the crucible, and the temperature and evaporation rate of the heating source were controlled to make the inorganic composite material -5 Pa) sublimates and deposits on the other side of the porous material to form a thin film. The crucible heating power is 250W and the evaporation rate is

[0083] S7: Cooling and solidification

[0084] The inorganic composite SEI layer formed by deposition is allowed to cool and solidify naturally. The solidified film is firmly bonded to the surface of the porous carbon material to form a stable inorganic composite SEI layer, thereby obtaining a lithium negative electrode with a multi-layer composite artificial SEI film.

[0085] Example 2

[0086] The difference between this embodiment and embodiment 1 is that the porous carbon material in steps S1-S3 is replaced by a porous silicon material with a pore diameter of about 70 nm, and the other aspects remain unchanged.

[0087] Example 3

[0088] The difference between this embodiment and embodiment 1 is that the porous carbon material in steps S1-S3 is replaced by a porous Si / C composite material with a pore diameter of about 70 nm, and the other aspects remain unchanged.

[0089] Example 4

[0090] The difference between this embodiment and embodiment 1 is that the inorganic composite material in step S5 is replaced by LiF:Li2O:Li3N:Li2CO3:Li 10 GeP2S 12 =1:1:1:1:1, other factors remain unchanged.

[0091] Example 5

[0092] The difference between this embodiment and embodiment 1 is that the inorganic composite material in step S5 is replaced by LiF:Li2O:Li3N:Li2CO3:Li3PO4=1:1:1:1:1, and the other aspects remain unchanged.

[0093] Example 6

[0094] The difference between this embodiment and embodiment 1 is that the inorganic composite material in step S5 is replaced by LiF:Li2O:Li3N:Li2CO3:Li2S=2:1:1:1:1, and the other aspects remain unchanged.

[0095] Comparative Example 1

[0096] The difference between this comparative example and Example 1 is that no porous material is used, and the inorganic composite material is replaced by a single LiF, and Li foil is directly used in the preparation, and after cleaning, LiF is directly evaporated onto the Li foil.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 1 is that no porous material is used, and the inorganic composite material is replaced by a single Li3N, and Li foil is directly used in the preparation, and after cleaning, Li3N is directly evaporated onto the Li foil.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 1 is that no porous material is used, and the inorganic composite material is replaced by a single Li2O, and Li foil is directly used in the preparation, and after cleaning, Li2O is directly evaporated onto the Li foil.

[0101] Comparative Example 4

[0102] The difference between this comparative example and Example 1 is that no lithium-philic layer is provided on the surface of the porous material.

[0103] Comparative Example 5

[0104] The difference between this comparative example and Example 1 is that the porous material is not subjected to nitridation treatment.

[0105] The lithium negative electrodes prepared in Examples 1-6 and Comparative Examples 1-5 were tested.

[0106] Assemble button cells for testing: the negative electrode is the lithium negative electrode obtained in the embodiment / comparative example, the positive electrode is LiFePO4, and the diameter of the lithium iron phosphate positive electrode is 12 mm, and the average load is about 2 mg cm -2, a separator (Celgard2400) was placed between the two electrodes, and the CR2032 button cell was assembled in an argon-filled glove box (U-Super MK4306-000-00, mikrouaTechnology Co., Ltd.), and the electrolyte was a carbonate-based electrolyte (1.0 mol l-1LiPF6, with ethyl carbonate (EC) / diethyl carbonate (DEC) as solvent, volume ratio 1:1). All charge / discharge tests were performed using a battery cycler (MIHW-200-160CH, Neware Technology Ltd.). Each charge / discharge time was fixed at 1 h, and after 3 activation cycles at 0.2 C, the battery was charged and discharged at 2.5 to 4.2 V (1 C = 170 mA g -1 ) voltage window. Electrochemical impedance spectroscopy (EIS) was performed using an electrochemical workstation (AutoLabPGSTAT302N, Metrohm) with a frequency range of 1×10 6 To 0.01Hz, the AC disturbance intensity is 5mV.

[0107] The test results are shown in Table 1.

[0108] Table 1. Test data of embodiments and comparative examples

[0109] project Cycle times Capacity retention rate Example 1 800 91.13% Example 2 800 90.71% Example 3 800 89.88% Example 4 800 89.33% Example 5 800 87.16% Example 6 800 88.79% Comparative Example 1 800 77.84% Comparative Example 2 800 77.83% Comparative Example 3 800 76.71% Comparative Example 4 800 74.92% Comparative Example 5 800 74.13%

[0110] It can be seen from the data in Table 1 that the capacity retention rate of the lithium negative electrode prepared in the embodiment of the present invention can reach more than 87% after 800 cycles, and has excellent cycle performance. However, the capacity retention rate of the comparative example after 800 cycles is significantly lower than that of the embodiment of the present invention. It can be seen that the present invention can improve the cycle performance, safety and overall efficiency of lithium batteries.

[0111] In terms of mechanical strength, the Poisson's ratio of the inorganic composite material in Example 1 is 0.17, and the Poisson's ratio of the single LiF in Comparative Example 1 is 0.2. The lower the Poisson's ratio, the better the material stiffness. Therefore, the present invention forms a strong artificial SEI layer by introducing an inorganic composite material layer, which can effectively improve the mechanical strength of the interface.

[0112] In terms of Li ion conductivity, the Li ion migration energy barrier of the inorganic composite material in Example 1 is 0.13, and the Li migration energy barrier of the single LiF in Comparative Example 1 is 0.17. The lower the migration energy barrier, the higher the Li ion conductivity. It can be seen that the present invention can effectively improve the Li ion conductivity by forming a solid artificial SEI layer through the introduction of an inorganic composite material layer.

[0113] Finally, it should be noted that the above specific embodiments are only used to explain in detail the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific implementation method of the present invention and is not used to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above specific embodiments, ordinary technicians in this field should understand that it is still possible to modify the technical solutions recorded in the above embodiments, or to replace or improve some or all of the technical features therein. These modifications, equivalent replacements and improvements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.

Claims

1. A lithium negative electrode having a multi-layer composite artificial SEI film, characterized in that: It comprises a porous material (1), a lithium-philic layer (2), lithium metal (3) and an inorganic composite material (4); A lithium-philic layer (2) and a lithium metal (3) are sequentially deposited on one side of the porous material (1), and an inorganic composite material is deposited on the other side of the porous material (1); The porous material (1) is at least one of a porous carbon material and a porous silicon material; The inorganic composite material (4) is LiF, Li2O, Li3N, Li2CO3, Li2S, Li 10 GeP2S 12 , Li3PO4, or at least five of the following.

2. The lithium negative electrode with a multi-layer composite artificial SEI film according to claim 1, characterized in that: The pore size of the porous material (1) is in the range of 50nm-100nm.

3. The lithium negative electrode with a multi-layer composite artificial SEI film according to claim 1, characterized in that: The material of the lithium-philic layer (2) is Ag.

4. The lithium negative electrode with a multi-layer composite artificial SEI film according to claim 1, characterized in that: The inorganic composite material (4) is LiF, Li2O, Li3N, Li2CO3 and Li2S, Li 10 GeP2S 12 A mixture consisting of any one of Li3PO4.

5. The lithium negative electrode with a multi-layer composite artificial SEI film according to claim 1, characterized in that: The mass ratio of each component in the inorganic composite material (4) is LiF:Li2O:Li3N:Li2CO3:(Li2S or Li 10 GeP2S 12 or Li3PO4)=(0.5-2):1:1:1:

1.

6. The method for preparing a lithium negative electrode having a multi-layer composite artificial SEI film according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: Cleaning the porous material to remove organic contaminants followed by nitriding; Depositing a lithium-philic material on one side of the porous material to form a lithium-philic layer film; depositing lithium metal on the lithiophilic layer; An inorganic composite material is deposited on the other side of the porous material, and the material is cooled and solidified to obtain a lithium negative electrode having a multi-layer composite artificial SEI film.

7. The method for preparing a lithium negative electrode having a multi-layer composite artificial SEI film according to claim 6, characterized in that: The cleaning of the porous material comprises the following steps: The porous material is cleaned with nitric acid or a mixed acid solution of nitric acid and sulfuric acid, cleaned with deionized water, dried, and finally heated to 400-800° C. in an inert atmosphere to remove organic pollutants on the surface.

8. The method for preparing a lithium negative electrode having a multi-layer composite artificial SEI film according to claim 6, characterized in that: The nitriding treatment comprises the following steps: The porous material is immersed in a urea or melamine solution, stirred and dried at 60-80°C, and then heat treated at 600-800°C in a nitrogen or ammonia atmosphere to introduce active nitrogen sites.

9. The method for preparing a lithium negative electrode having a multi-layer composite artificial SEI film according to claim 6, characterized in that: The deposition adopts vacuum evaporation coating technology.

10. Use of the multi-layer composite artificial SEI film according to any one of claims 1 to 5 or the multi-layer composite artificial SEI film obtained by the preparation method according to any one of claims 6 to 9 in a lithium battery.

Citation Information

Patent Citations

  • Efficient negative electrode structure for prolonging cycle lifetime of lithium metal battery

    CN106207191A

  • Preparation method of self-supporting iron-nickel alloy decorated nitrogen-doped porous carbon nanofiber lithium metal negative electrode framework material

    CN114388769A

  • Method for constructing composite lithium metal negative electrode through surface modification of foamy copper and application of composite lithium metal negative electrode

    CN114975880A

  • Lithium composite material and preparation method and application thereof

    CN116314736A

  • Implementation method of lithium-loving three-dimensional structure lithium-free negative electrode

    CN116314850A

Cited By

  • Core-shell material, preparation method thereof and negative electrode material

    CN120901282A